Prairie Fire, Kansas : a Ralph Compton western - Compton, Ralph; Shirley, John, 1953- (Compton, Ralph. Sundown Riders, 2020)
"Fresh from a successful trail drive, cattle hand Seth Coe is feeling flush, especially after a lucky streak at the poker table. But his good fortune earns him a dangerous enemy, notorious tinhorn gambler Hannibal Fisher, who is none too happy about being cleaned out. The innocent Coe starts the long ride back to Texas with big plans to buy his own ranch. All he needs now, he figures, is a wife. To his amazement, in tiny Prairie Fire, Kansas he meets the perfect woman, his childhood love Josette Dubois. But she is under the thumb of her brutal father, who will stop at nothing to prevent her happiness, including killing Coe--that is, if Fisher doesn't get there first. . ."--Provided by publisher.